Metabolic biomarkers in early detection of gestational diabetes mellitus: a prospective diagnostic accuracy study - Tigli, Alihan; Baykus, Yakup; Deniz, Rulin; Selcuk, Kevser Tari; Sener, Nazli; Degirmenci, Yasemin Ercan; Aydin, Suleyman (Frontiers Media Sa, 2026)
Background and objectives: Early diagnosis of gestational diabetes mellitus (GDM) is essential for the prevention of maternal and neonatal complications. In this study, we aimed to investigate the value of first trimester inflammatory markers (Neutrophil-to-Lymphocyte Ratio (NLR), Platelet-to-Lymphocyte Ratio (PLR), Monocyte-to-Lymphocyte Ratio (MLR), Neutrophil-to-Monocyte Ratio (NMR)), HDL-based metabolic inflammation indicators (Lymphocyte-to-High-Density Lipoprotein Cholesterol Ratio (LHR), Monocyte-to-High-Density Lipoprotein Cholesterol Ratio (MHR), Granulocyte-to-High-Density Lipoprotein Cholesterol Ratio (GHR)) and metabolic indices (Atherogenic Index of Plasma (AIP), Triglyceride-Glucose Index (TyG)) in predicting GDM. Materials and methods: Between December 2024 and October 2025, 250 pregnant women were included in this prospective diagnostic accuracy study conducted at Band & imath;rma Onyedi Eyl & uuml;l University Hospital. First trimester (10-14 weeks) complete blood count, fasting glucose and lipid profile were recorded. NLR, PLR, MLR, NMR, LHR, MHR, GHR, AIP and TyG indices were calculated. GDM was diagnosed with 75 g Oral Glucose Tolerance Test (OGTT) at 24-28 weeks according to International Association of the Diabetes and Pregnancy Study Groups (IADPSG) criteria. Diagnostic performance was evaluated by ROC analysis and significance level was taken as p < 0.05. Results: The prevalence of GDM was 18.0% (n = 45). Age, body weight, Body Mass Index (BMI) and parity were significantly higher in the GDM group (p < 0.05). Biomarker averages did not differ significantly between the two groups (p > 0.05). According to Receiver Operating Characteristic (ROC) analysis, the Area Under the Curve (AUC) values were NLR (0.470), PLR (0.490), MLR (0.474), NMR (0.481), LHR (0.567), MHR (0.506), GHR (0.466), AIP (0.561) and TyG (0.573). None of them exceeded the threshold value of 0.70. Conclusion: LHR, MHR, AIP and TyG indices are of limited value in predicting GDM. These markers cannot be used alone in the early period. OGTT is still the most reliable diagnostic method. More specific biomarkers and multicenter studies are needed for early diagnosis.
Keywords: atherogenic index plasma; early diagnosis; gestational diabetes mellitus; HDL-based ratios; inflammatory markers; triglyceride-glucose index